Answer: x = - 4
y = - 6
Explanation:
The given system of linear equations is expressed as
- x + 2y = - 8- - - - - - - - - - - - -1
3x - y = - 6 - - - - - - - - - - - -2
We would eliminate x by multiplying equation 1 by 3 and equation 2 by 1. It becomes
- 3x + 6y = - 24- - - - - - - - - - -3
3x - y = - 6- - - - - - - - - - - -4
Adding equation 3 to equation 4, it becomes
5y = - 30
Dividing the left hand side and the right hand side of the equation by 3, it becomes
5y/5 = - 30/5
y = - 6
Substituting y = - 6 into equation 2, it becomes
3x - - 6 = - 6
3x + 6 =- 6
Subtracting 6 from the left hand side and the right hand side of the equation, it becomes
3x + 6 - 6 = - 6 - 6
3x = - 12
Dividing the left hand side and the right hand side of the equation by 3, it becomes
3x/3 = - 12/3
x = - 4